Dyspnea improvement in patients with lung diseases in a single session of mindful breathing: a randomized controlled study - Ng, Diana Leh-Ching; Chai, Chee Shee; Liam, Chong Kin; Pang, Yong Kek; Tan, Seng Beng; Wong, Tat Seng (Wiley Online Library, 2018)
Background and Aims: Mindful breathing has been practised in recent decades and there is a lack of study for it as a nonpharmacological method in improving dyspnea. This study was to assess the efficacy of mindful breathing in improvement of dyspnea score, oxygen saturation and respiratory rate in patients with lung diseases.